Cable-Driven Parallel Robots Proceedings of the Third International Conference on Cable-Driven Parallel Robots (Mechanisms and Machine Science, 2018)
This book presents proceedings of the third international conference in this field, continuing the success of the previous events. The peer-reviewed and the selected papers are arranged to make the proposed book the most recent and complete overview on the State-of-the-Art in Cable-Driven Parallel Robots! The conference took place 2017 in Quebec, QC, Canada,.